1993
DOI: 10.1212/wnl.43.12.2581
|View full text |Cite
|
Sign up to set email alerts
|

Cytosol protein kinase C downregulation in fibroblasts from Alzheimer's disease patients

Abstract: We attempted to determine whether changes in protein kinase C (PKC) activity in Alzheimer's disease (AD) brains are also present in cultured skin fibroblasts from living patients. Biopsies collected from shoulder skin were transferred to culture plates with an appropriate growth medium, and histone-directed PKC activity as well as phorbol ester binding were individually determined in soluble and particulate fractions prepared from AD and non-AD fibroblast cell lines. Binding experiments indicated that PKC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 0 publications
4
55
0
1
Order By: Relevance
“…In addition, data from a number of laboratories, including ours, have demonstrated a decreased PKC activity in sporadic AD fibroblasts. 10 We also observed an increase of the Kd (dissociation constant) for phorbol ester binding in the cytosolic fraction of AD fibroblasts, which suggested an alteration in the characteristics of the kinase. Subsequently, the described changes in PKC were correlated to a specific 30% reduction in PKCa immunoreactivity.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, data from a number of laboratories, including ours, have demonstrated a decreased PKC activity in sporadic AD fibroblasts. 10 We also observed an increase of the Kd (dissociation constant) for phorbol ester binding in the cytosolic fraction of AD fibroblasts, which suggested an alteration in the characteristics of the kinase. Subsequently, the described changes in PKC were correlated to a specific 30% reduction in PKCa immunoreactivity.…”
Section: Introductionmentioning
confidence: 57%
“…6,7 The extensive studies on regulation of APP processing by PKC suggest that the Ab forming amyloidogenic pathway and the non-amyloidogenic a-secretase pathway are balanced, the latter being activated by PKC. Although this simple view of APP metabolism may not fully reflect the complexity of the system, 22 PKC-defective pathways have been described in peripheral tissues of sporadic AD patients 10,23 and these defects have been associated with aberrant APP processing. 11 The central role of PKC in APP metabolism is therefore also connected to the fact that defective PKC is one of the most consistent findings in AD brain and peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Because experiments were performed in a cell-free condition, Ah must have interacted with PKC in a direct manner, and to our knowledge, this is the first demonstration of such a direct interaction between Ah and PKC. Although previous studies have demonstrated degradation of PKC (Favit et al, 1998), reduction of PKC-mediated phosphorylation (Chauhan et al, 1991;Govoni et al, 1993), and decrease of PKCa membrane translocation (Pakaski et al, 2002) by Ah, these studies were performed using cultured cells or a liposome system; thus, it was uncertain whether the effects of Ah were direct or indirect. When deletion (DKGA) or point mutation (GGA) was induced into the putative PKC pseudosubstrate sequence, Ah lost its effects on PKC phosphorylation in the cell-free system, indicating that the putative sequence is indeed responsible for direct Ah -PKC interaction.…”
Section: Discussionmentioning
confidence: 99%
“…PKC-mediated ␣-secretase activation is responsible for TNF-␣ generation. Furthermore, deficits of PKC isozymes have been found in AD brain tissues (8) and skin fibroblasts (9)(10)(11), as have deficits of PKC-mediated phosphorylation of MAPK (12). Therefore, we investigated a molecular biomarker that assays both MAPK Erk1 and Erk2 phosphorylation in response to the inflammatory signaling molecule bradykinin (BK), which activates PKC pathways.…”
mentioning
confidence: 99%